Monitoring of Space Debris Rotation Based on Photometry - Koshkin, N.; Shakun, L.; Korobeynikova, E.; Melikyants, S.; Strakhova, S.; Dragomiretsky, V.; Ryabov, A.; Golubovskaya, T.; Terpan, S. (Одеські астрономічні публікації, 2018)
The number of spacecraft and space debris (SD) in orbit has become so great that there is a real threat to flight safety. The task of precision calculation of the upcoming positions of any space objects (SO) in orbit in order to predict dangerous mutual approaches and to solve practical tasks has become topical. For the development of a modern orbit propagation model and the associated unified forecast of the evolution of orientation and rotation of an uncontrolled satellite, it is necessary to rely on long-term series of high-quality measurements and their analysis. At present, the direction of research on determining the state of SO rotation around a center of mass has become more and more developed. In our work, we analyze the results of photometric observations of several large objects of space debris obtained at the Astronomical Observatory of Odessa University using the KT-50 telescope during the last six years or more. The results of the evolution of the rotation rate and orientation of the Topex/Poseidon, Envisat, Oicets, Cosmos-2487 (Kondor-E) and Sich-2 satellites are presented.